Endomorphin analog exhibited superiority in alleviating neuropathic hyperalgesia via weak activation of NMDA receptors. Issue 6 (31st July 2020) - Ma, Mengtao; Wang, Zhaojuan; Wang, Jing; Wei, Shuang; Cui, Jiaming; Wang, Yuan; Luo, Keyao; Zhao, Long; Liu, Xin; Wang, Rui
Abstract: Morphine is a key drug for the treatment of pain but its side effects limit its clinical application. MEL‐0614, an endomorphin‐1 analog, has fewer side effects than morphine in addition to its powerful analgesic effect. In this study, we measured the effect of morphine and MEL‐0614 on hyperalgesia (7 days) and neuropathic allodynia (14 days) after thermal, mechanical, and cold stimulation. We found that after four and eight consecutive days of intrathecal administration (1, 3, and 10 nmol), morphine induced severe hyperalgesia and neuropathic allodynia, respectively. MEL‐0614 did not induce hyperalgesia at low doses (1 and 3 nmol) and had a mitigating effect on morphine‐induced neuropathic exacerbations in spared nerve injury mice. Hyperalgesia was blocked by Dynorphin A (1–17) antibody but not by an opioid receptor antagonist. To explore the reasons for the different results of morphine and MEL‐0614, we used quantitative PCR and immunofluorescence to explore the effects of both on N‐methyl‐D‐aspartate (NMDA) receptor subtype 2B (NR2B), microglia marker iba‐1, and inflammatory mediators. After 8 days of consecutive administration, morphine (10 nmol) promoted an increase in the number of NR2B, iba‐1, and inflammatory mediators in the spinal cord of mice. MEL‐0614 (10 nmol) had no significant effect on these factors, and after co‐administration with morphine, the expression of NR2B, iba‐1, and inflammatory mediators was lower than that with morphine injection alone. Our research showed the advantage of MEL‐0614 in terms of hyperalgesia and neuropathic allodynia, which may provide clinical relief of hyperalgesia and neuropathic allodynia caused by morphine. Abstract : The graphical abstract of the study; Morphine induced more severe hyperalgesia and neuropathic allodynia than MEL‐0614 by activating NMDA receptors and microglia. Morphine acts on NMDA receptors to activate the receptor but MEL‐0614 has no such effect. Morphine binds to to TLR4 on microglia will activate microglia and upregulation of P2X4R on microglia leads to increased BDNF release. BDNF up‐regulates KCC2 by acting on neuronal TrκB receptors. TrκB signalling potentiates glutamatergic excitation via NMDA receptors. TNF and IL‐1β could also act on NMDA receptors to enhance its activity. All of the results led to increased neuronal excitability, resulting in hyperalgesia.